Penerapan Learning Organization Di Program Studi Ilmu Administrasi Negara Universitas Maritim Raja Ali Haji - Pranedya Derina Visanty (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The presence of UMRAH as the only maritime-based university is very in line with the potential of the Riau Islands Province which has thousands of islands and a very wide sea area, and is also in line with President Jokowi's nawacita who wants to make Indonesia a maritime axis. Therefore, it is very necessary for UMRAH to prepare well institutionally to meet competency standards at the national and international levels. This research uses the method of literature study or library research which is a research method carried out by collecting, studying, and analyzing references or sources obtained in writing or in writing and various references such as books, journals, articles, documents, and other existing sources of information that are significant with the topic/title to be researched. The results showed that the application of learning organizations in the State Administration Study Program FISIP UMRAH is felt to have increased and developed where it can be seen that many activities have been carried out, including the Implementation of the Independent Learning Program-Independent Campus, Thesis Supervisor Exchange, Lecturer Exchange, Student Exchange, Research Collaboration, Journal Manager Collaboration, Curriculum Development and Practicum Activities, Collaboration Community Service.